Practices of the circular economy in Community Source projects: A preliminary study - Almigheerbi, Tereq Salahi (Praktyki w zakresie gospodarki o obiegu zamkniętym w projektach Community Source: badanie wstępne, 2020)
Nowadays, the ‘Circular Economy’ (CE) is a modern topic that benefits business, society, and the environment. So far, the application of the CE has been restricted to certain areas that do not include the field of Information System development. From this point of view, the ‘community source’ model can be considered as an area to investigate the practices of the CE in Information System development. The community source model is a new model in software development that is intermediate between two well-known models (closed and open source systems). The practices of the CE found in projects that follow the community source model is then a potential area of scientific interest. A project was launched to comprehensively analyse this phenomenon. This paper presents the results of the preliminary study to initially explore the CE practices in community source projects. During the fieldwork, community source projects in EU countries were surveyed. The preliminary study concluded that practices such as recycling and resource-sharing are those that can arguably be found in these projects. As a term, a new kind of material has emerged, ‘soft material’ along with the typical kinds of material previously identified in the CE, namely biological and technical materials. The paper also briefly discusses the strategy of circular community in dealing with e-waste management
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 4 (58), s. 9-20
Keywords: informatyka ekonomiczna